Family‐based treatment for adolescent anorexia nervosa: What happens to rates of comorbid diagnoses?. (29th January 2020) - Trainor, Claire; Gorrell, Sasha; Hughes, Elizabeth K.; Sawyer, Susan M.; Burton, Claire; Grange, Daniel Le
Abstract: Objective: Rates of psychiatric comorbidity are elevated in adolescents with anorexia nervosa, but little is known about how psychiatric comorbidity changes following family‐based treatment (FBT). Methods: Adolescents with anorexia nervosa ( N = 107) enrolled in a randomized controlled trial comparing two forms of FBT completed the Mini International Neuropsychiatric Interview for Children and Adolescents at baseline and end of treatment. Analyses tested whether baseline comorbid diagnoses predicted the presence of comorbid diagnoses at end of treatment and if baseline eating disorder psychopathology impacted this association. Results: Rates of comorbid diagnoses decreased from 54% at baseline to 26% at end of treatment. Logistic regression analyses indicated that individuals with multiple comorbid diagnoses at baseline were more likely to meet criteria for a comorbid condition at end of treatment ( b = 2.00, p  < .05). Individuals with reported psychotropic medication use were less likely to meet criteria for a comorbid condition at end of treatment ( b = −1.63, p = .04). Diagnostic rates for major depressive disorder, generalized anxiety disorder, and panic disorder/agoraphobia decreased following FBT. Conclusions: Findings suggest that FBT for adolescent anorexia nervosa may aid in the resolution of some co‐occurring psychiatric diagnoses. Continued research is needed to understand factors contributing to comorbid symptom improvement throughout treatment.